THEATRICAL PRODUCTIONS BASED ON FOLK TALES AS A MEANS OF SOCIAL AND CULTURAL EDUCATION AMONG SCHOOLCHILDREN - Ataev Utkir (International Engineering Journal For Research & Development, 2022)
This article is about the peculiarities of the development of social and cultural education among schoolchildren by means of theatrical performances based on folk tales, which contributes to the development of children's interest, love for books, reading, words, stimulating creative, aesthetic abilities, activating the possibility of self-expression, self-affirmation of the child.